Penatalaksanaan Pemeriksaan CT-Scan Cardiac Dengan Modifikasi Tatalaksana Pada Kasus Heart Rate Tinggi Di Rumah Sakit Primaya Tangerang - Amraini Amraini; Edwien Setiawan (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Cardiac CT-Scan is a series of examinations to produce cardiac imaging aimed at identifying fatty deposits or calcium in the coronary arteries, so that a better treatment can be determined for the patient. Heart rate is the number of heartbeats per unit time, usually expressed in minutes / beats per minute (bpm) which is based on the number of ventricular contractions. Cardiac CT Scan examination with high heart rate can be modified using GE Revolution Maxima CT-Scan software using SnapShot Freeze Technology with extended cardiac helical pitch scanning mode which provides a significant dose reduction for higher heart rate scans. CT Scan Cardiac begins with patient preparation, tools and materials, patient positioning and examination protocols as well as the reconstruction process. This study used a qualitative research method with a case study approach using one patient.